Lauantai-ilta MTV:llä 1981–2005 – Kaupallisen television strategiat ohjelmasijoittelussa - Maiju Kannisto (Lähikuva-yhdistys, 2022)
Schedule defines the everyday specificities of television. Saturday is an evening for entertainment. This article examines the program slot of Saturday evening on MTV, between the years 1981 and 2005. MTV is a commercial television network, which was founded in 1957. At the beginning, its programs were broadcast on two channels, owned by the public service company Yleisradio. Only after 1989, MTV was allocated its own channel.  Television broadcast on the new channel started in 1993. This article analyses the scheduling strategies of commercial television. It discusses the continuity of genres and production culture, and the effects that target audiences have on scheduling.
Domestic entertainment programs were the core of the broadcast output of Saturday evenings. For MTV, specific Saturday entertainment meant variety. Variety is characteristic of MTV’s evening schedule throughout the research period. In this article, I define two points of rupture in MTV’s scheduling strategy: first, the allocation of MTV’s own channel in 1989, and second, the strategic preparation for digitalization, multi-channel network, and intermedia cooperation at the end of the 1990s. The main result of the article is the introduction of three periods of scheduling and production around the before mentioned ruptures: 1) the period of cooperation in the 1980s, 2) the period of competition in the 1990s, and 3) the period of branding in the 2000s.